Ginsenoside Rb1 ameliorates Staphylococcus aureus-induced Acute Lung Injury through attenuating NF-κB and MAPK activation. (July 2019) - Shaukat, Aftab; Guo, Ying-fang; Jiang, Kangfeng; Zhao, Gan; Wu, Haichong; Zhang, Tao; Yang, Yaping; Guo, Shuai; Yang, Chao; Zahoor, Arshad; Akhtar, Muhammad; Umar, Talha; et al.
Abstract: Acute lung injury (ALI) is clinically characterized by excessive inflammation leading to acute respiratory distress syndrome (ARDS), having high morbidity and mortality both in human and animals. Ginsenoside Rb1 (Rb1) is a major primary bioactive component extracted by Panax ginseng, which has numerous pharmacological functions such as anti-cancer, anti-inflammatory, and antioxidant. However, the anti-inflammatory effects of Rb1 in Staphylococcus aureus ( S. aureus )-induced ALI in mice have not been investigated. The aim of the current study was to determine the anti-inflammatory influence of Rb1 on S. aureus -induced ALI in mice, and to explore its possible underlying principle mechanisms in RAW 264.7 macrophage cells. The results of physical morphology, histopathological variation and wet-to-dry weight ratio of lungs revealed that Rb1 significantly attenuated S. aureus -induced lung injury. Furthermore, qPCR results displayed that Rb1 inhibited IL-1β, IL-6 and TNF-α production both in vivo and in vitro. The activation of Toll-like receptor 2 (TLR2) by S. aureus was inhibited by application of Rb1 as confirmed by results of immunofluorescence assay. The expression of NF- k B and MAPK signaling proteins revealed that Rb1 significantly attenuated the phosphorylation of p65, ERK, as well as JNK. Altogether, the results of this experiment presented that Rb1 has ability to protect S. aureus -induced ALI in mice by attenuating TLR-2-mediated NF- k B and MAPK signaling pathways. Consequently, Rb-1 might be a potential medicine in the treatment of S. aureus -induced lung inflammation. Highlights: Acute lung injury (ALI) is an excessive inflammation leading to acute respiratory distress syndrome (ARDS), Ginsenoside Rb1 (Rb1) is a major primary bioactive component extracted by Panax ginseng. QPCR results displayed that Rb1 inhibited IL-1 β, IL-6 and TNF- α production both in vivo and in vitro. The results presented that Rb1 has ability to protect S. aureus -induced ALI by attenuating TLR-2 mediated NF- k B and MAPK signaling